Dependence of phenotype and chemiluminescent activity of monocytes on the Tregulatory cells content in patients with kidney cancer - A. A. Savchenko (Medicinskaâ Immunologiâ, 2020)
The aim of this work was to reveal the interrelations between the number of T regulatory cells (Tregs) in patients with kidney cancer (KC) and phenotype of peripheral blood monocytes and their capacities to produce ROS. Patients with KC (T3N0M0, clear cell type) were examined prior to surgical treatment. Tregs phenotype and blood monocytes were identified by flow cytometry. ROS production of purified monocytes was carried out through the determination of lucigenin- and luminol-dependent spontaneous and zymosan-induced chemiluminescence activity. It has been found that the relative number of Tregs within total lymphocyte subset in KC patients was increased if compared to control values (in KC patients — Me = 6.3%). Then the patients were divided into two groups according to the median of Tregs number (less and more than 6.3%). The most pronounced changes in the phenotype of monocytes and their chemiluminescent activity were found in KC patients with the Tregs count of less than 6.3%. Our findings suggest that low frequency of Tregs in the periphery was associated with increased relative numbers of “intermediate” and “non-classical” (“pro-inflammatory”) monocytes as it was shown on the samples from patients with KC with a low level of Tregs. According to our data, both groups of KC patients had low levels of HLA-DR expression when comparing to control group. Furthermore, both groups of patients had decreased rates of HLA-DR and CD64 co-expressing cells. Changes in the phenotype of monocytes in patients with KC were closely linked with imbalance in ROS production. Thus, the monocytes spontaneous superoxide radical (primary ROS) synthesis in KC patients with a low Treg numbers were characterized by redused NADPH-oxidase activation time and increased level of its activity if compared to patients with a high Treg rates in peripheral blood. Next, the activation index for lucigenin-dependent chemiluminescence in KC patients was reduced, as well as it was independent of circulating Tregs rates and was determined apparently by the insufficiency of metabolic reserves. Similarly, spontaneous secondary ROS production by the monocytes in KC patients was lower then in healthy controls and was also independent of circulating Tregs rates. Finally, the induced secondary ROS synthesis and activation index for their synthesis in monocytes were reduced only in patients with KC with a low number of Tregs in the blood. In general, the characteristics of the chemiluminescent reaction of monocytes in patients with KC determined the imbalance in peripheral blood monocytes primary and secondary ROS production. Monocytes in patients with KC with a low number of Tregs in the blood were characterized by more pro-inflammatory activity due to the rapid activation and intensity of the synthesis of primary ROS.